PENGARUH ORIENTASI PASAR TERHADAP KINERJA PEMASARAN WISATA ALAM - Johannes Johannes; Alex Chandra Erta (DIGEST MARKETING, 2018)
The purpose of this study is to analyze market orientation towards marketing performance on natural tourism. Samples are business that engaged in the tourism sector in Kerinci and Merangin district as sample that consists of 48 units. Data were collected by questionnaires and analyzed by using multiple regression analysis. The results showed that market orientation (customer orientation, competitor orientation, coordination between functions) have significant effect on the marketing performance. Natural tourism business hence should make more focus on customer in one hand but pay more attention to their competitor especially out of Jambi Province. To do that, intensive coordination should be more implemented between related stakeholders.